Hypoparathyroidism, deafness and renal dysplasia syndrome caused by a GATA3 splice site mutation leading to the activation of a cryptic splice site - Gonçalves, Catarina I.; Carriço, Josianne N.; Omar, Omneya M.; Abdalla, Ebtesam; Lemos, Manuel C. (Frontiers in Endocrinology, 2023)
The HDR syndrome is a rare autosomal dominant disorder characterised by Hypoparathyroidism, Deafness, and Renal dysplasia, and is caused by inactivating heterozygous germline mutations in the GATA3 gene. We report an 11-year-old girl with HDR syndrome caused by a heterozygous mutation located at the splice acceptor site of exon 5 of the GATA3 gene (NM_001002295.2: c.925-1G>T). Functional studies using a minigene assay showed that this splice site mutation abolished the normal splicing of the GATA3 pre-mRNA and led to the use of a cryptic splice acceptor site, resulting in the loss of the first seven nucleotides (TCTGCAG) of exon 5 in the GATA3 mRNA. These findings increase the understanding of the mechanisms by which GATA3 splicing mutations can cause HDR syndrome.